2017
DOI: 10.18632/oncotarget.15912
|View full text |Cite
|
Sign up to set email alerts
|

Ponatinib promotes a G1 cell-cycle arrest of merlin/NF2-deficient human schwann cells

Abstract: Neurofibromatosis type 2 (NF2) is a genetic syndrome that predisposes individuals to multiple benign tumors of the central and peripheral nervous systems, including vestibular schwannomas. Currently, there are no FDA approved drug therapies for NF2. Loss of function of merlin encoded by the NF2 tumor suppressor gene leads to activation of multiple mitogenic signaling cascades, including platelet-derived growth factor receptor (PDGFR) and SRC in Schwann cells. The goal of this study was to determine whether pon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…Earlier studies have shown activation of Src in NF2 wild-type vs NF2 deficient Schwann cell lines 38 and treatment of merlin-deficient mouse Schwann cell lines also identified dasatinib as a potentially effective agent based on the results of a high-throughput drug screen 39 however, this study focused on a more specific Src inhibitor, saracatinib, in combination with the c-Met inhibitor cabozantinib 39 . Dasatinib is FDA-approved for treatment of acute lymphocytic leukemia and chronic myeloid leukemia with mutant Abl kinase expression, and is shown to inhibit oncogenic and invasive processes in blood cancers and solid tumors 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown activation of Src in NF2 wild-type vs NF2 deficient Schwann cell lines 38 and treatment of merlin-deficient mouse Schwann cell lines also identified dasatinib as a potentially effective agent based on the results of a high-throughput drug screen 39 however, this study focused on a more specific Src inhibitor, saracatinib, in combination with the c-Met inhibitor cabozantinib 39 . Dasatinib is FDA-approved for treatment of acute lymphocytic leukemia and chronic myeloid leukemia with mutant Abl kinase expression, and is shown to inhibit oncogenic and invasive processes in blood cancers and solid tumors 40 .…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that ponatinib would have been a much more potent inhibitor for HCC cells had it not activated the PDK1/Akt/mTOR pathway. There are conflicting reports on if ponatinib inhibits [20,44,45] or activates [41] Akt signaling in the literature. The discrepancy suggests that the effects of ponatinib on Akt signaling may be dependent on cell signaling background.…”
Section: Discussionmentioning
confidence: 99%
“…Ponatinib (AP24534), an orally available and potent multi-targeted kinase inhibitor, has been approved by the Food and Drug Administration (FDA) to treat imatinib-resistant patients with chronic myelogenous leukemia [17,18]. Ponatinib inhibits both native and mutant forms of BCR-ABL, including the T315I gatekeeper mutant that is resistant to other tyrosine-kinase inhibitors (TKIs) [19,20]. Besides its activity against BCR-ABL, ponatinib also inhibits approximately 50 other PTKs with IC 50 values below 100 nM, including many kinases in the PDGFR, Src, VEGFR, Eph receptor (EphR), and FGFR families [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petrilli and colleagues reported that ponatinib is a potential therapeutic compound for the treatment of neurofibromatosis type 2 (NF2) [ 72 ], which is a genetic disorder causing multiple benign tumours in the central and peripheral nervous systems, including vestibular schwannomas. NF2 is caused by mutations in the NF2 gene encoding the tumour suppressor protein merlin (or schwannomin), which regulates many kinase pathways.…”
Section: Solid Tumoursmentioning
confidence: 99%